MANAGEMENT OF SECONDARY GLAUCOMA DUE TO SENILE CATARACT IN 56 YEARS OLD MAN - Arnia Arnia (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2015)
Glaucoma is the second leading major cause of blindness in the world after cataract. The morbidity is estimated at ± 70 million people. According to the Indonesian Ministry of Health survey reported in 1996, glaucoma is the third major cause of blindness in both eyes after cataract and blindness due to refractive error, with a prevalence of approximately 0.16% of the population. A man, 56 years old, present with a redness left eye with pain around the eyes and headace since ± 2 days before hospital admission. The eye pain first felt 6 months ago. Patient feel increasingly blur vision, often seen misty shadows and glare on the left eye. From examination on the left oculi found visual acuity was 0, the conjunctiva bulbi obtained mix injection, corneal edema (+), pupil rounded and at central, mydriasis (+), light reflex (-), cloudy lens, ocular tension increased with palpation. Patient diagnosed with secondary glaucoma et causa senile cataract. Management of this patient was hyperosmotic agents or manitol 250 mg/4 hours,timolol/betaxolol 0,25 to 0,50% eye drop 2 times a day; pilocarpine 2% eye drop 3 times a day; acetazolamide 250 mg tabs 3-4 times a day, KSR tab 1 a day, and planned for operation procedure if intraocular pressure has decreased. [J Agromed Unila 2015;2(1):52-56]Keywords: cataract, glaucoma, management